2017
DOI: 10.1002/bem.22063
|View full text |Cite
|
Sign up to set email alerts
|

Influence of radiofrequency–electromagnetic waves from 3rd‐generation cellular phones on fertilization and embryo development in mice

Abstract: The purpose of this study was to evaluate the effects of 3rd‐generation (3G) cellular phone radiofrequency–electromagnetic wave (RF‐EMW) exposure on fertilization and embryogenesis in mice. Oocytes and spermatozoa were exposed to 3G cellular phone RF‐EMWs, 1.95 GHz wideband code division multiple access, at a specific absorption rate of 2 mW/g for 60 min, or to sham exposure. After RF‐EMW exposure, in vitro fertilization and intracytoplasmic sperm injection were performed. Rates of fertilization, embryogenesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 32 publications
(34 reference statements)
0
2
0
Order By: Relevance
“…Finally, exposure of mouse oocytes and sperm to RF for 60 min prior to in vitro fertilization techniques had no effects on fertilization rates, blastocyst formation, and chromosomal aberration [ 185 ].…”
Section: Emf Effects On Female Reproductive System and Fertilitymentioning
confidence: 99%
“…Finally, exposure of mouse oocytes and sperm to RF for 60 min prior to in vitro fertilization techniques had no effects on fertilization rates, blastocyst formation, and chromosomal aberration [ 185 ].…”
Section: Emf Effects On Female Reproductive System and Fertilitymentioning
confidence: 99%
“…The number of cases regarding the effect of RF on mammal brain functioning, cognitive behaviour (Isa et al, 2013), blood brain barrier related issues (Sirav & Seyhan, 2016) have been found to be signi cant in some research papers. Besides that, the change in heart rhythms (Page et al, 2016), sperm production levels (Singh et al, 2018), oxidative stress (Siddiqi & Nazwani, 2024), hormone levels (Bektas et al, 2024), hepatic (Fahmy & Mohammed, 2021), renal functions (Borzoueisileh et al, 2020), embryonic developments (Suzuki et al, 2017) etc. have been observed, loss in DNA integrity (Panagopoulos et al, 2021).…”
Section: Introductionmentioning
confidence: 99%